2019
DOI: 10.15587/1729-4061.2019.179900
|View full text |Cite
|
Sign up to set email alerts
|

Studying the tribological properties of mated materials C61900 - A48-25BC1.25BNo. 25 in composite oils containing geomodifiers

Abstract: З розвитком дисперсних систем в трибологiї створилась можливiсть ефективно використовувати функцiональнi добавки до мастильних матерiалiв у виглядi геомодифiкаторiв. При впровадженнi композицiйних олив з геомодифiкаторами не потрiбно виконувати конструктивнi змiни спряжень деталей машин, але їх зносостiйкiсть i припрацьовуванiсть збiльшується. Це потребує проведення експериментальних трибологiчних дослiджень. Запропоновано використання геомодифiкатора KGМF-1+олеїнової кислоди в якостi функцiональної добавки до… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…It should be noted that each characteristic requires individual research on the concentration and content of fibers in the polymer. Several related studies examined the issue of improving the characteristics of tribo-mated parts by using a lubricant environment and tribo-active additives [25], geomodifiers [26], a complex involving lithium and fluoride soaps [27]. The tribological properties of mated parts with these additives are improved by 10...18 % only if there is an oil base, but, under dry friction modes, it is necessary to consider the possibility of adding to the matrix.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It should be noted that each characteristic requires individual research on the concentration and content of fibers in the polymer. Several related studies examined the issue of improving the characteristics of tribo-mated parts by using a lubricant environment and tribo-active additives [25], geomodifiers [26], a complex involving lithium and fluoride soaps [27]. The tribological properties of mated parts with these additives are improved by 10...18 % only if there is an oil base, but, under dry friction modes, it is necessary to consider the possibility of adding to the matrix.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The non-stable processes in the operation of friction nodes in automotive equipment in the presence of motor lubricants were considered in papers [6][7][8][9]. The experimental studies have established the effect of various additives to oils on the stabilization of friction forces and reducing the wear of rubbing surfaces.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Expressions (14), (15) describe the right-hand (high-frequency) side of the threesomes of disturbances (8). The low-frequency part of these threesomes with the energy ΔE competes with two high-frequency components in view of the sharp increase in the role of forced thermal radiation relative to the spontaneous one with an increase in the wavelength.…”
Section: The Pseudo-equilibrium and Collapse Models Of Contact Disturmentioning
confidence: 99%
“…With the development of nanomaterials, in tribology, it was possible to effectively use functional additives in the form of geomodifiers [1,2]. It was revealed that oils modified with nanomaterials, which form dispersed systems in lubricants, increase the durability of working surfaces of different types of tribosystems.…”
Section: Introductionmentioning
confidence: 99%